Shear capacity of high performance fiber reinforced concrete I-beams. (30th December 2017) - Pansuk, Withit; Nguyen, Thuc N.; Sato, Yasushiko; Den Uijl, J.A.; Walraven, J.C.
Highlights: Presence of steel fiber significantly increases the shear capacity of HPFRC beams. Combination of fibers and high volumes of steel bars shows a less influence of fibers. AFGC-Sétra 2002 and Model code 2010 presented the safety of the shear design formulas. Shear crack displacement of the HPFRC strongly depends on the amount of fiber. Abstract: An experimental program was carried out to investigate the shear capacity of High-Performance Fiber-Reinforced Concrete (HPFRC) I-beams. The main parameters were assigned as the fiber content and presence of shear reinforcement. To study the effect of these main parameters on the shear capacity, testing of six I-beams and other control specimens was conducted. It can be observed from the results of the experimental study that the presence of fibers and shear reinforcement significantly improves the ultimate capacity and structural behavior of HPFRC members. Finally, the experimental results are discussed, and the shear capacity of HPFRC can be estimated by extending the code provisions stated in AFGC-Sétra 2013.